Chemical Composition, Antioxidant Potential and Enzymes Inhibitory Properties of Globe Artichoke By‐Products. Issue 9 (21st August 2020) - Rejeb, Ines Ben; Dhen, Nahla; Gargouri, Mohamed; Boulila, Abdennacer
Abstract: In this study, chemical composition and in vitro biological activities of artichoke by‐products (leaves, floral stems and bracts) issued from two Tunisian varieties were evaluated. Analysis was performed by means of high‐performance liquid chromatography with diode array detection coupled to electrospray ionization mass spectrometric (LC/DAD/ESI‐MS). Total phenolic (TPC) and flavonoid (TFC) contents as well as the antioxidant activity conducted by three complementary methods, DPPH, ABTS and FRAP tests, were performed for each sample. Enzyme inhibitory effects against acetylcholinesterase, butyrylcholinesterase and α ‐amylase were also studied. Results showed that TPC and TFC varied according to variety as well as the plant part. Bracts presented the highest TPC values (10–15 mg GAE/g DW), while leaves were distinguished by the highest TFC values (52–58 mg EQ/g DW). In vitro assays showed that Violet d'Hyères bracts and Blanc d'Oran leaves present the most antioxidant activities (30.040 and 20.428 mgET/gDW, respectively, by the DPPH method). Leaves demonstrated the highest acetylcholinesterase and butyrylcholinesterase inhibitory effects. Moreover, all organs displayed a noticeable inhibition towards α ‐amylase. LC/DAD/MS analysis revealed that artichoke by‐products are a potential source of biopharmaceuticals such as luteolin derivatives from leaves and mono/dicaffeoylquinic acids in the other parts. This research demonstrates that globe artichoke by‐products, unexploited in our country, are a promising source of natural health promoting compounds with potential applications in the food and pharmaceutical industries. Abstract :